PENGARUH GAYA KEPEMIMPINAN, MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN UPT BALAI PENGEMBANGAN PENDIDIKAN KEJURUAN (UPT BP DIKJUR) SEMARANG - E. Indah Arrum Triwijayanti, 09.05.51.0010; Sutomo, Y. (Students Journal of Economic and Management, 2013)
This research aims to examine and analyze the effect of leadership style, motivation and discipline toward perfomance of employees working on the performance of Balai Pengembangan Pendidikan Kejuruan (UPT BPDIKJUR). Data collection was done through questionnaires and performed on 100 employees of Balai Pengembangan Pendidikan Kejuruan (UPT BP DIKJUR). In this case, the researchers did not use sampling techniques because the samples studied is the whole of the population, also called census. technique testing data used in this research include the validity test using the Kaiser-Mayer Olkin Measure of Sampling Adequacy (KMO) andLoading factors. Results addressing the value of Kaiser-Mayer Olkin Measure of Sampling Adequacy (KMO) qualified for further analysis to declared invalid. Further analysis using multiple regression analysis to explain the relationship between these variables. The result is a hypothesis that shows leadership style has positive and significant impact on the performance of employees, while positive and significant motivation on employeeperformance and work discipline and significant positive effect on employee performance.Key words: leadership style, Motivation, work discipline and employee performance.